2016
DOI: 10.1080/10826084.2016.1219373
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Ecstasy/MDMA/“Molly” Use in a Sample of Nightclub and Dance Festival Attendees in New York City

Abstract: Background Ecstasy (MDMA) use has regained popularity in the United States, particularly in the form of “Molly,” which is often marketed as pure MDMA. Surveys have generally not included “Molly” in the definition of ecstasy, so rates of use may be underestimated. As popularity of ecstasy increases, research is needed to examine use among those at highest risk for use—nightlife attendees. Methods We surveyed 679 young adults (age 18–25) entering nightclubs and festivals holding electronic dance music (EDM) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 49 publications
1
43
0
1
Order By: Relevance
“…These results add to and corroborate a previous hair study which found higher levels of party attendance are related to a higher risk of testing positive for synthetic cathinones (Palamar, Salomone, et al, 2016). These results also corroborate multiple previous studies that have found higher levels of party attendance are related to robust increases in risk of using a variety of drugs including synthetic cathinones and other NPS (Palamar, Acosta, Ompad, et al, 2016; Palamar, Acosta, Sherman, et al, 2016; Palamar, Barratt, et al, 2016; Palamar et al, 2015). …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results add to and corroborate a previous hair study which found higher levels of party attendance are related to a higher risk of testing positive for synthetic cathinones (Palamar, Salomone, et al, 2016). These results also corroborate multiple previous studies that have found higher levels of party attendance are related to robust increases in risk of using a variety of drugs including synthetic cathinones and other NPS (Palamar, Acosta, Ompad, et al, 2016; Palamar, Acosta, Sherman, et al, 2016; Palamar, Barratt, et al, 2016; Palamar et al, 2015). …”
Section: Discussionsupporting
confidence: 90%
“…A recent national survey of Australian dance festival-attending adults found that 78.1% of recent users reported using an illicit drug at their last-attended festival, and of users, 85.1% reported use of ecstasy (Hughes et al, 2017). A recent study of EDM party attendees in New York City (NYC) estimated lifetime use of ecstasy/MDMA or “Molly” amongst young adult (age 18-25) attendees to be 42.8% (95% CI: 32.8, 52.7) (Palamar, Acosta, Ompad, & Cleland, 2016). “Molly” is a common street name for powder or crystalline MDMA in the US; thus, since ecstasy and Molly are both street names for MDMA, some epidemiology surveys in the US now use these terms interchangeably or in combination (Palamar, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding to the literature on polydrug use among ecstasy users (Halkitis et al, 2007; Martins et al, 2007; Palamar et al, 2017b; Wu et al, 2006), 70% of ecstasy users in this sample reported using at least 2 other substances in the past year, and reporting use of 5–8 substances increased across time. The proportion of past-year use of marijuana, LSD, ketamine, and/or DMT/AMT/Foxy increased, with greatest relative increases in DMT/AMT/Foxy use (i.e., 314%) from 2007/08 to 2013/14.…”
Section: Discussionmentioning
confidence: 94%
“…While ecstasy use appears to be most prevalent in the electronic dance music scene (Hughes et al, 2017; Palamar et al, 2017b), examining recent shifts in demographic characteristics of users can inform potential needed changes to strategies for prevention efforts, public health messages, and harm reduction. User demographics may have shifted over time as the form of the drug has largely changed from pills to powder; individuals who continue to use ecstasy despite decreased prevalence could need focused efforts to reduce related harms.…”
Section: Introductionmentioning
confidence: 99%